2023
DOI: 10.1111/jnc.15822
|View full text |Cite
|
Sign up to set email alerts
|

Recent insights into the networking of CLN genes and proteins in mammalian cells

Abstract: Ceroid lipofuscinosis neuronal (CLN) genes encode 13 proteins that localize throughout the endomembrane system to regulate a variety of cellular processes. In humans, mutations in CLN genes cause a devastating form of neurodegeneration called neuronal ceroid lipofuscinosis (NCL), commonly known as Batten disease. Each CLN gene is associated with a specific subtype of the disease that differ from each other in severity and age of onset. The NCLs affect all ages and ethnicities worldwide but primarily affect chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…CLN proteins are distributed throughout the endomembrane system and regulate a variety of cellular processes related to ion homeostasis, autophagy, lipid metabolism, and protein trafficking [ 125 ]. To date, fourteen CLN proteins (CLN1-14) have been identified and characterized [ 126 , 127 ]. Among these, CLN6 and CLN8 localize to the membrane of the ER, where they regulate lysosomal enzyme recruitment and lysosome biogenesis [ 128 ], while CLN1, CLN2, CLN3, CLN5, and CLN10 localize to lysosomes and function as soluble enzymes [ 129 , 130 , 131 ].…”
Section: Lysosomal Ion Channelsmentioning
confidence: 99%
“…CLN proteins are distributed throughout the endomembrane system and regulate a variety of cellular processes related to ion homeostasis, autophagy, lipid metabolism, and protein trafficking [ 125 ]. To date, fourteen CLN proteins (CLN1-14) have been identified and characterized [ 126 , 127 ]. Among these, CLN6 and CLN8 localize to the membrane of the ER, where they regulate lysosomal enzyme recruitment and lysosome biogenesis [ 128 ], while CLN1, CLN2, CLN3, CLN5, and CLN10 localize to lysosomes and function as soluble enzymes [ 129 , 130 , 131 ].…”
Section: Lysosomal Ion Channelsmentioning
confidence: 99%
“…CLN genes encode thirteen proteins that localize throughout the endomembrane system to regulate a variety of cellular processes. Mutations in CLN genes cause a devastating form of neurodegeneration commonly known as Batten disease (Huber, 2023). It was recently shown that the ER/Golgi-localized ZIP7 colocalizes with CLN6 (Grubman et al, 2014).…”
Section: Zip Family In the Brainmentioning
confidence: 99%
“…The localizations and functions of CLN proteins have been studied in several model organisms 20,21 . One such organism, the social amoeba Dictyostelium discoideum , has made important contributions to our understanding of CLN gene and protein networking and the roles of CLN genes in protein secretion 22–24 . On a broader level, D. discoideum is recognized as an exceptional model system for studying human lysosomal and trafficking diseases given the high degree of conservation of lysosomes and trafficking pathways between D. discoideum and humans 25 …”
Section: Introductionmentioning
confidence: 99%